Taxonomic investigation of monilophytes from North Waziristan Tribal District KP, Pakistan - Aziz, Tariq; Gul, Alia; Alam, Jan (International Journal of Applied and Experimental Biology, 2024)
Floristic surveys and assessment of relationships between species richness and elevational gradients help in developing more efficient conserving strategies for biodiversity under climate change. North Waziristan Tribal District (NWD) has been identified as the second largest district in FATA. The study area encompasses diverse altitudes, ranging from 600 m to over 3000 m. Due to its distinct geological history, low temperature, and rich biodiversity, the North Waziristan Tribal District gives an excellent opportunity to assess taxonomic distribution of ferns. Field visits were conducted during 2021, thoroughly documenting fern species along with essential field-related characteristics such as habits, habitats, GPS coordinates, etc. Floristic studies of ferns (monilophytes) from NWD showed that it has an exceptionally diverse monilophyte flora. A total of 114 fern specimens were collected during these field visits. After a comprehensive examination, 17 species distributed across 13 genera and 7 families were identified. The predominant family was Pteridaceae, comprising six species, followed by Aspleniaceae and Thelypteridaceae with three species each. Additionally, Dryopteridaceae accounted for two species, while the remaining three had only one species each. Asplenium was the leading genus, documented with three species, followed by Pteris, Cheilanthes, and Adiantum, each with two species. Finally, a dichotomous key was made based on morphological, anatomical, and palynological characters for identification and characterization purposes. In terms of altitude, the highest number of taxa were observed at elevations above 2200 m, while the lowest species count was reported between 600 -1000 m. Species richness of ferns reached to a maximum at moderate elevations, which could have been due to combination of moderately low temperature and high humidity. Ethnobotanical documentation revealed eight species, six genera, and four families within the study area.